Public Perceptions and Knowledge of, and Responses to, Bats in Urban Areas in Peninsular Malaysia. (2nd November 2019) - Lim, Voon-Ching; Wilson, John-James
ABSTRACT: Urbanization has resulted in the loss of natural habitat for many bat species, often placing bats in close proximity to humans. Bats are generally perceived as agricultural and medical pests, despite providing ecosystem services including seed dispersal and pollination. Understanding public perceptions and knowledge of bats as well as responses to bats is necessary for developing suitable educational programs to support bat conservation. Here we examined the urban communities' knowledge of bats and how they perceive and respond to bats in Peninsular Malaysia. A questionnaire survey of 340 respondents revealed that women generally had better knowledge of bats compared with men. Respondents with tertiary education and knowledge of the ecological roles of bats tended to support the conservation of bats. In addition, there was low demand for bat meat in this region. Family-based educational programs could help to improve the perception of bats among women and increase knowledge of bats among men. Educational programs highlighting the biology and ecology of bats should be conducted at primary and secondary schools to raise awareness of bats among children who could share this knowledge of bats with their family members.